Family Firms and Labor Market Regulation. Issue 2 (21st June 2019) - Bennedsen, Morten; Huang, Sterling; Wagner, Hannes F; Zeume, Stefan
Abstract: In a panel across twenty-eight countries over 10 years, we show that family firms on average enjoy performance advantages over nonfamily firms only when labor markets are less regulated. We confirm this result in a matched firm sample using a survey-based instrument as a family control. Furthermore, family firms exhibit lower variation in employment levels in less-regulated labor markets, supporting the notion that labor relations drive family firms' performance advantages. Our results are consistent with the notion that both family ownership and labor market reforms provide employment protection and thus partly substitute as governance mechanisms. Received December 17, 2018; editorial decision April 3, 2019 by Editor Andrew Ellul.